2010
DOI: 10.1124/dmd.110.033951
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism, Excretion, and Pharmacokinetics of Oral Brivanib in Patients with Advanced or Metastatic Solid Tumors

Abstract: ABSTRACT:The goal of this study was to evaluate the pharmacokinetics, mass balance, metabolism, routes and extent of elimination, and safety of a single oral dose of 14

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…Urine and feces were collected from each patient over intervals through 288 h postdose. Further details of this study were reported by Mekhail et al (2010).…”
Section: 4]triazin-4-yloxy)-1h-indole-2-carboxylic Acid (M26) Were Smentioning
confidence: 99%
“…Urine and feces were collected from each patient over intervals through 288 h postdose. Further details of this study were reported by Mekhail et al (2010).…”
Section: 4]triazin-4-yloxy)-1h-indole-2-carboxylic Acid (M26) Were Smentioning
confidence: 99%
“…Brivanib, an oral, selective dual inhibitor of FGFR and VEGF receptor (VEGFR) tyrosine kinases, has shown antitumor activity in preclinical models of various cancers, including HCC (23)(24)(25)(26)(27). Brivanib has a half-life of 12 hours and is administered once daily at a dose of 800 mg.…”
Section: Introductionmentioning
confidence: 99%
“…Brivanib has manageable safety profiles in long-term toxicology and clinical studies (Mekhail et al, 2010;Park et al, 2011). The toxicology profile of the enantiomeric metabolite was not directly studied in preclinical species.…”
Section: Metabolite Profiles Of Incubation Mixtures Of [mentioning
confidence: 99%
“…The biotransformation and disposition of brivanib in animals and humans have been characterized previously (Mekhail et al, 2010;Gong et al, 2011). After oral doses of [ 14 C]brivanib alaninate to rats, monkeys, and humans, the radioactive dose was mainly cleared by metabolism, and the majority of drug-derived radioactivity was excreted in feces (Gong et al, 2011).…”
Section: Introductionmentioning
confidence: 99%